HISTOGENESIS OF HUMAN FETAL STOMACH AT VARIOUS GESTATIONAL AGES – AN OBSERVATIONAL STUDY: Histogenesis - RAO, RAPETI RAMANA; GARA, RAMADEVI; RAO B, NARASINGA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Knowledge on timelines of structural and histological development of fetal stomach helps in the diagnosis of abnormalities (duplication cyst of the pylorus, heterotopic pancreatic tissue, etc.,) and weighing interventions as an option. The present study was undertaken to establish the timelines of the developmental process of stomach (e.g., appearance of curvatures, gastric pit, gastric glands, and various cell types) correlating with the gestational age. Methods: Fifty normal, aborted and unclaimed fetuses were obtained from local private and government hospitals observing all formalities. The tissues of 3–5 mm thickness were taken and preserved in 10% formalin for 72 h, followed by tissue processing and staining with hematoxylin eosin and periodic acid Schiff and observations were made under microscope. Results: Lesser and greater curvatures appeared in the first trimester. All the four layers and gastric pits were observed at 16th week, cuboidal epithelium turns columnar and nidus of gastric glands, circular muscular layer submucuosa noted by 18th week, longitudinal layer of muscle appeared at 20th week, parietal, zymogenand mucus neck cells observed by 24th week in fundus, and body oblique muscle was evident by 28th week and near adult pattern seen by 32nd week of gestation. Conclusion: From the available literature, very few studies have reported regarding histogenesis of human fetal stomach in India. The present study is one such to supplement the known data and knowledge regarding histogenesis of human fetal stomach and help in diagnosis and treatment of related congenital anomalies.